DEVELOPING CRITICAL THINKING THROUGH THE TEACHING OF LITERATURE - I Gusti Ayu Gde Sosiowati (Universitas Negeri Padang, 2015)
Richards (2006) states that the purpose of learning language is to master the communicative competence, meaning that by the end of the leaming process, the students should be able to produce proper language in any genre and in any situation. However, that competence alone, without accompanied by the ability to perform critical thinking will end in the conversation talking about explicit information only. It can not be denied that understanding the implicit infbrmation r'vill be challenging and making the conversation interesting. Halpern (cited on l5 March 2015) states that critical thinking refers to the use of cognitive skills or strategies that increase the probability of a desirable outcome. It is the kind of thinking which is involved in solving problems- formulating inferences, calculating likelihoods, and making decisions.The purpose of this article is to show that literary work can be used to develop critical thinking and at the same time is able to improve the students' English proficiency. Literary works, in this case short stories are good teaching materials for the purpose since they contain implicit or unsaid information that must be understood by the students. The idea of developing critical thinking is in line with one of the skills mentioned by Harmer (2006), that is interpreting text. He says that interpreting text enables the students to see beyond the literal meaning of words in a passage, using a variety clues to understand rvhat the writer is implying.Thus, it can be said that literary work can be used as the teaching material to improve both language proficiency and critical thinking.